Membangun Aplikasi Belajar Qur’an Berbasis Android - Chairul Rizal; Barany Fachri; Supiyandi Supiyandi; Rusli Halil Nasution (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
At present, mobile devices are developing so rapidly that they have various functions, as well as for multitasking and also have a system such as a computer, so they are also commonly referred to as Smart Devices. Smartphones circulating in the market generally the most in demand are android devices, from android devices are widely used for utilization, the use of smartphone functions, among others, is used for several purposes, so that its development is increasingly widespread, one of which is learning media. The method applied in the learning media is the Asy Syafi'i method where the method was developed at Ma'had Imam Asy Syafi'I and uses the waterfall method in research because this method is very easy to apply in several research cases. The results obtained in this study are creating an Android-based Al-Qur'an learning media application to facilitate today's society where all activities cannot be separated from gadgets.